Interaksi Genotipe dan P60 terhadap Karakter Kuantitatif Cabai Besar (Capsicum annuum L.) - Siti Hafsah; Syamsuddin Syamsuddin; Nur Azizah Dly; Firdaus Firdaus (Universitas Teuku Umar, 2022)
This study was to identify the interaction of several genotypes and the concentration of P60 on the quantitative characters of large chili peppers and to determine the correlation between these two factors. This study used a 3x4 factorial randomized block design with 3 replications. The first factor is the genotype of large chili consisting of 3 levels, namely G1 : F7 Gada, G2 : Anies and G3 : Seloka 4-10-2-2. While the second factor is the concentration of P60 (K) consisting of 4 levels, namely K0 : 0%, K1 : 0,6%, K2 : 1,2% and K3 : 1,8%. Parameters observed were plant height at 30 DAP, stem diameter at 30 DAP, number of productive branches at 30 DAP, dichotomous height at 30 DAP, flowering age, number of fruit per plant, length per fruit, diameter per fruit, weight per fruit, thickness. Meat per fruit and yield potential. The results showed that there was an interaction between several genotypes pf large chili and the concentration of P60 which had a significant effect on the number of productive branches aged 30 DAP. The best treatment combination was found in the Seloka 4-10-2-2 treatment with a P60 concentration of 1,2%.Key words : Genotypes, Large Chili , Pseudomonas fluorescens, productive, Anies